Review of Prevention and Management Strategies for Pressure Sores and Ulcers in Immobilized Orthopedic Patients - Ramya Mathew; Asha Cynthia D'sa; Nishitha Marina Machado; Chaithra Nayak (RGUHS Journal of Nursing Sciences)
Pressure sores also called lsquopressure ulcersrsquo or lsquobedsoresrsquo develop on various parts of the body due to prolonged pressure which can lead to skin and tissue damage. These injuries are a cause for concern in immobilized orthopaedic patients due to limited mobility and prolonged immobility. This systematic review aimed to evaluate interventions and strategies for preventing and managing pressure sores in this population. We reviewed seventeen research articles including case studies cohort studies randomized controlled trials and systematic reviews. The reviewed studies underscore several crucial elements in preventing and managing pressure ulcers in immobilized orthopedic patients including structured education and training care bundles evidence-based guidelines innovative interventions managing risk factors nursing care comprehensive skin care a positive attitude and a proactive approach. In conclusion pressure ulcers are a significant concern in immobilized orthopaedic patients but with the implementation of evidence-based strategies their incidence can be significantly reduced. Structured educational initiatives care bundles evidence-based practice guidelines and innovative interventions along with the crucial role of nurses are key components in preventing and managing pressure ulcers. Healthcare providers can enhance patient outcomes improve the quality of care and lower healthcare costs related to pressure ulcer management by implementing these strategies.